ANALYZING THE EFFECTIVENESS OF EXCELLENT SERVICE ON OPERATIONAL PERFORMANCE OF GRAB-BIKE DRIVER (CASE STUDY AT GRAB ARMY SULUT) - Adrian, Mersondy T.; Karamoy, Herman; Tielung, Maria V. J. (Universitas Sam Ratulangi, 2021)
The escalation of online motorcycle driver services, has opened the job opportunity for the society. Unfortunately, the increasing number of the drivers, did not followed with provide the skill and the service strategies that relevant with their job characteristics. The objective of excellent service is to harmonize the attitude, attention, action, appearance, ability, and accountability to make the situation of mutualism for all. The aim of this study is to know about the effectiveness of excellent service on the operational activities of the grab-bike drivers. In order to achieve these objectives, the researcher got information from 11 informants, using qualitative study which is in-depth interview and observation, and uses purposive sampling technique. The results showed that the excellent service at research object has been running well and effective to influence the drivers to work better, excellent service gives a positive impact to the driver, and the drivers get the opportunity to learn new strategy and improve their quality when operate. The recommendation is excellent service is very important and cannot be separated with work activities, so in order to be more competitive excellent service must always be improved and apply.Â Keyword: excellent service, operational performance, human resources.